Lump Sum Moving Cost and Aggregate Office Space Use - Gerbert Romijn (Tinbergen Institute, 1997)
When firms decide to change office space use, in many instances this involves relocation. Relocation involves sizablecosts to the firm that can to a large extent be characterized as lump sum, i.e. independent of the change in demand. Inthis paper we propose and solve a model of the demand for office space with lump sum adjustment costs at the firm level.The optimal policy for a firm is a so-called control band policy, or (s,S)-rule: leave office space use unchanged until thedifference between actual office space use and desired office space use exceeds a certain threshold. Desired office spaceuse is defined as the office space use that would result if no frictions were present and conforms to a model were actualoffice space depends only on relevant current state variables. Next we go on to investigate the aggregate implications ofthis lumpy microeconomic behaviour using a stochastic aggregation framework of Bertola and Caballero (1994).The lumpy behaviour at the firm level implies that aggregate demand for office space is a time-varying weighted averageof the current and lagged state of the economy. Only a fraction of aggregate demand depends on the current state of theeconomy. Furthermore, the magnitude of this fraction also depends on the current state of the economy. We use ourmodel on office space market data for The Netherlands. We find that desired office space use is more volatile than actualoffice space use and does not track actual office space use very well. Aggregate office space implied by our model tracksactual office space use much closer, indicating that the gap between theoretical desired office space use and actual officespace use can be accounted for by lumpy adjustment at the firm level.
Keywords: 330; Betriebliche Standortwahl; Büro; Niederlande